2021
DOI: 10.3390/ijms22041707
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transporter LAT1 (SLC7A5) Mediates MeHg-Induced Oxidative Stress Defense in the Human Placental Cell Line HTR-8/SVneo

Abstract: The placental barrier can protect the fetus from contact with harmful substances. The potent neurotoxin methylmercury (MeHg), however, is very efficiently transported across the placenta. Our previous data suggested that L-type amino acid transporter (LAT)1 is involved in placental MeHg uptake, accepting MeHg-L-cysteine conjugates as substrate due to structural similarity to methionine. The aim of the present study was to investigate the antioxidant defense of placental cells to MeHg exposure and the role of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Likewise; LAT1 plays an active role in metabolic processes involved in T -cell differentiation and effector function ( Sinclair et al, 2013 ), facilitating the metabolic demands of T -cells to propagate a pro-inflammatory response; which; if persistent, has been linked to T2D pathogenesis ( Jagannathan-Bogdan et al, 2011 ; Shoelson et al, 2006 ). On the other hand; in vitro studies using a human placental cell line found LAT1 has a protective role against oxidative stress and inflammation induced by metal toxicity ( Granitzer et al, 2021 ). Taken together; depending on the cellular context, LAT1 may have a fundamental role in environmental toxicant-induced oxidative damage and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise; LAT1 plays an active role in metabolic processes involved in T -cell differentiation and effector function ( Sinclair et al, 2013 ), facilitating the metabolic demands of T -cells to propagate a pro-inflammatory response; which; if persistent, has been linked to T2D pathogenesis ( Jagannathan-Bogdan et al, 2011 ; Shoelson et al, 2006 ). On the other hand; in vitro studies using a human placental cell line found LAT1 has a protective role against oxidative stress and inflammation induced by metal toxicity ( Granitzer et al, 2021 ). Taken together; depending on the cellular context, LAT1 may have a fundamental role in environmental toxicant-induced oxidative damage and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Hg is highly toxic and is still present in electrical and electronic devices and is also contained in some thermometers specifically for the measurement of high temperatures. Methylmercury (MeHg) is the principal constituent of organic Hg and damages foetal development since it crosses the placenta and blood-brain barrier (Clarkson and Magos, 2006;Granitzer et al, 2021). MeHg is present in high levels in seafood and some fishes.…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…The formation of thiol-MeHg bonds is likely also responsible for the placental accumulation because MeHg, similar to Hg 2+ , is known to bind to thiol-containing molecules—for example, proteins, cysteine, and glutathione. Recently the amino acid transporter LAT1 (SLC7A5) has been involved in the transport of MeHg in HTR-8/SV-neo cells [ 59 ]. Regarding the actual mechanism of action of MeHg, it has been demonstrated that 1 μg/mL methylmercury decreased viability, proliferation, and migration and led to the decreased expression of SOD1 in the HTR8/SV-neo trophoblast cells [ 60 ].…”
Section: Mechanisms Of Oxidative Stress Induction By Environmental Pollutantsmentioning
confidence: 99%